Onychomycosis due to Cunninghamella bertholletiae in an Immunocompetent Male from Central India - Karuna Tadepalli; Pradeep Kumar Gupta; Dinesh P. Asati; Debasis Biswas (Case Reports in Infectious Diseases)
Onychomycosis is a fungal infection of nails seen frequently in immune competent and immune compromised patients due to dermatophytes, Candida spp., Fusarium spp., Scopulariopsis brevicaulis, Penicillium spp., and Aspergillus spp. We report a case of onychomycosis in a young immunocompetent male who presented onycholysis of a solitary nail without inflammation. The etiological agent was diagnosed to be Cunninghamella bertholletiae, a fungus pertaining to the order Mucorales (subdivision Mucoromycotina) and known for some of the invasive lesions among immunocompromised patients. This case demonstrates the association of onychomycosis with Cunninghamella bertholletiae in an immune competent individual, not reported so far.